STUDI VARIABILITAS KEJADIAN SIKLON TROPIS SERTA HUBUNGANNYA DENGAN EL NIÃO-SOUTHERN OSCILLATION (ENSO) DAN INDIAN OCEAN DIPOLE (IOD) DI PERAIRAN SEKITAR INDONESIA - Raharjo, Adyarto
This final project describes the period, frequency, intensity and also the trajectory of tropical cyclone events near Indonesian Waters which consist of Western North Pasific Ocean, Northern Indian Ocean, and Southern Indian Ocean for 32 years from 1977 untill 2008 based on Joint Typhoon Warning Center (JTWC) annual report. This study is correlated with the El Niño-Southern Oscillation (ENSO) events based on sea surface temperature anomalies ENSO index in Niño-3.4 as well as Indian Ocean Dipole Mode (IODM) events based dipole mode index in Indian Ocean. Cross correlation analysis between number of tropical cyclones and ENSO/dipole mode index was used to observe the relevance between ENSO/IODM and tropical cyclone frequencies. Tropical cyclone initial position analysis was also used to investigate trajectories change during El Niño/ In Western North Pasific, there is a tendency where the intense tropical cyclone events (category 3 untill 5) more (less) frequent during El Niño ( La Niña/dipole mode periods. La Niña) periods that indicated from the positive significant correlations (r > 0.7) between number of intense tropical cyclone with ENSO index. There is also negative significant correlation (r < -0.4) between number of tropical storms that show the tendency more (less) frequent tropical storms during El Niño (La Niña) periods. Tropical cyclone formation shifted more to east at 140o E along with decrease of tropical cyclone formations in 120o E-140o E region during El Niño periods, conversely happen during La Niña periods. In Northern Indian Ocean there is negative significant correlations (r < -0.2) between dipole mode index and number of tropical cyclones that indicated the increase number of tropical cyclones during negative dipole periods. There is no significant correlations (|r| < 0.1) between dipole mode index and number of tropical cyclones in Southern Indian Ocean that cause by different occurance period.